Just Talk : Narratives of Psychotherapy. - Furst, Lilian R. (The University Press of Kentucky, 2015)
While countless memoirs have been written about depression and therapy, no one has examined how the ""talking cure"" of psychotherapy is presented in novels and other works of literature. Beginning with an overview of the principles of psychotherapy and its growing use as a treatment for mental and emotional disorders, Lilian Furst addresses the patient's view of the value of talk. Patients' portrayals of psychotherapy in literary works range from serious to satirical and from comic to ironic, with some descriptions verging on the grotesque. Furst identifies the overtalkers, undertalkers, and.